Superconducting properties of Barium, BA substitution in BSCCO-2223 / Amirah Natasha Ishak - Ishak, Amirah Natasha (Faculty Of Applied Sciences, 2017)
In this study, the superconducting properties of barium, Ba substitution in BSCCO2223 have been investigated by using four-point probe and X-ray Diffraction analysis. Ba was incorporated in the calcium, Ca2+ site with concentrations of x = 0.00, 0.02, 0.05 and 0.10. Samples of x = 0.02, 0.05 am 0.10 have higher Tc value compared to the pure BSCCO-2223 (x = 0.00). The optimum Ba concentration that has the highest Tc value which is 99 K is x = 0.05. It can be simplified that barium substitution in BSCCO-2223 enhances the Tc value. XRD pattern SIDWS a lot of improvement of the peaks since the low-peak (2212) decreases while high-peak (2223) increases with the increases of Ba concentration